Isolasi dan identifikasi ekspresi protein rekombinan granule-1 (GRA-1) Toxoplasma gondii isolat lokal - Hevi Wihadmadyatami; Rini Widayanti; Wayan Tunas Artama (Jurnal Sain Veteriner, 2011)
Toxoplasmosis is a diseases caused by intracellular protozoa called Toxoplasma gondii.